Cardiac Regeneration and Tumor Growth—What Do They Have in Common? - Dicks, Severin; Jürgensen, Lonny; Leuschner, Florian; Hassel, David; Andrieux, Geoffroy; Boerries, Melanie (Frontiers in Genetics, 2020)
Acute myocardial infarction is a leading cause of death. Unlike most adult mammals, zebrafish have the capability to almost fully regenerate their hearts after injury. In contrast, ischemic damage in adult human and mouse hearts usually results in scar tissue. mRNA-Sequencing (Seq) and miRNA-Seq analyses of heart regeneration in zebrafish over time showed that the process can be divided into three phases: the first phase represents dedifferentiation and proliferation of cells, the second phase is characterized by migration and in the third phase cell signals indicate heart development and differentiation. The first two phases seem to share major similarities with tumor development and growth. To gain more insight into these similarities between cardiac regeneration and tumor development and growth, we used patient matched tumor normal (“healthy”) RNA-Seq data for several tumor entities from The Cancer Genome Atlas (TCGA). Subsequently, RNA data were processed using the same pipeline for both the zebrafish samples and tumor datasets. Functional analysis showed that multiple Gene Ontology Terms (GO terms) are involved in both early stage cardiac regeneration and tumor development/growth across multiple tumor entities. These GO terms are mostly associated with cell cycle processes. Further analysis showed that orthologous genes are the same key players that regulated these changes in both diseases. We also observed that GO terms associated with heart development in the third late phase of cardiac regeneration are downregulated in the tumor entities. Taken together, our analysis illustrates similarities between cardiac remodeling and tumor progression.